A High-Precision Transfer of Time and RF Frequency via the Fiber-Optic Link Based on Secure Encryption - Guo, Xinxing; Qiu, Yanfeng; Liu, Bo; Kong, Weicheng; Liu, Tao; Dong, Ruifang; Zhang, Shougang (Applied sciences, 2022)
This paper presents a high-precision transfer system of time and RF frequency via the fiber optic link based on secure encryption. On the basis of the two-way time transfer of optical fiber, a security strategy composed of an SM2 encryption algorithm is introduced, which can resist the security risk of time information being tampered with. The experimental results show that the developed picosecond-precision fiber-optic time transfer equipment can ensure high stability while realizing the encryption function. Time synchronization stability in terms of time deviation (TDEV) of 1 PPS can reach around 10.7 ps at 1 s and 7.1 ps at 10 s averaging time. The stability of the 10 MHz frequency can reach around 4.7 × 10−12 at 1 s and 1.1 × 10−12 at 10 s averaging time. There is no significant difference in time transfer accuracy, compared with unencrypted conditions. Furthermore, this paper realizes a ring time transfer network via a 150 km fiber-optic link with three nodes using three devices. The TDEV of 1PPS can reach around 20.8 ps at 1s averaging time. This paper provides a reference to establish a high-precision, safe, and stable time synchronization fiber network in the future.